Methimazole-Induced neutropenic gingival ulcerations and necrosis in a middle-aged female: A case report with clinical management - Ritika Arora; Anamika Sharma; Deepakshi Dimri; Himani Sharma (Wolters Kluwer Medknow Publications, 2018)
One of the major manifestations of methimazole-induced neutropenia or agranulocytosis is diffuse gingival ulceration and necrosis. The aim of this case report is to be familiar with drug-induced neutropenia and its associated oral manifestations and the healing of the gingiva after proper treatment.